A&T Gujarat Implementation Research Baseline Survey 2022: Panchayati Raj Institution Members - International Food Policy Research Institute (International Food Policy Research Institute, 2025)
This dataset originates from the survey of PRI Members Survey, conducted as part of the baseline for the Alive & Thrive (A&T) impact evaluation study in Gujarat, India. The study aimed to assess the effectiveness of systems-strengthening interventions and local governance engagement in improving the quality and co-coverage of health and nutrition services, particularly during the first 1,000 days of a child's life.